Ethnic segregation between schools is it increasing or decreasing in England? - Harris, Richard; Johnston, Ron 1941-2020 (Bristol University Press, 2020)
There is an enduring belief amongst some that segregation is worsening and undermining social cohesion, and that this is especially visible in the growing divides between the schools in which our children are educated. This book uses up-to-date evidence to interrogate some of the controversial claims made by the 2016 Casey Review, providing an analysis of contemporary patterns of ethnic, residential and social segregation, and looking at the ways that these changing geographies interact with each other
Title from publisher's bibliographic system (viewed on 19 Mar 2021)
Keywords: Segregation in education / Great Britain; Discrimination in education / Great Britain